Salmonella Typhi–Induced Septic Shock and Acute Respiratory Distress Syndrome in a Previously Healthy Teenage Patient Treated With High-Dose Dexamethasone. (28th May 2016) - Ugas, Melissa Brosset; Carroll, Timothy; Kovar, Lacey; Chavez-Bueno, Susana
Typhoid fever is commonly characterized by fever and abdominal pain. Rare complications include intestinal hemorrhage, bowel perforation, delirium, obtundation, and septic shock. Herein we describe the case of a previously healthy 16-year-old male without history of travel, diagnosed with typhoid fever complicated by septic shock and acute respiratory distress syndrome treated with high-dose dexamethasone. This case details severe complications of typhoid fever that are uncommonly seen in developed countries, and the successful response to high-dose dexamethasone as adjunct therapy. High-dose dexamethasone treatment has reportedly decreased Salmonella Typhi mortality, but controlled studies specifically performed in children are lacking, and most reports of its use are over 30 years old and all have originated in developing countries. Providers should include Salmonella Typhi in the differential diagnosis of the pediatric patient with fever, severe abdominal pain, and enteritis, and be aware of its potentially severe complications and the limited data on safety and efficacy of adjunctive therapies that can be considered in addition to antibiotics.